2020
DOI: 10.1029/2019jg005502
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Nitrogen Sources in a Tropical Urban Estuary

Abstract: Tropical urban estuaries are severely understudied. Little is known about the basic biogeochemical cycles and dominant ecosystem processes in these waterbodies, which are often low lying and heavily modified. The San Juan Bay Estuary (SJBE) in San Juan, Puerto Rico, is an example of such a system. Over the past 80 years, a portion of the estuary has filled in, changing the hydrodynamics and negatively affecting water quality. Here we sought to document these changes using ecological and biogeochemical measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 48 publications
1
22
0
Order By: Relevance
“…and Yangzte River in China (Jiang & Li, 2014;Xu et al, 2005;Yin et al, 2017) have reported that DNRA dominates when the sulfide transition zone is near the sediment surface. A few studies in developing countries, such as Thailand and Indonesia (Dong et al, 2011), support the more extreme findings of Oczkowski et al (2020) of high DNRA and low-to-undetected levels of DNF, suggesting that low-latitude estuaries, like low-nutrient estuaries, likely respond differently to environmental controls than their temperate and even their subtropical counterparts.…”
Section: 1029/2020jg005766mentioning
confidence: 99%
See 4 more Smart Citations
“…and Yangzte River in China (Jiang & Li, 2014;Xu et al, 2005;Yin et al, 2017) have reported that DNRA dominates when the sulfide transition zone is near the sediment surface. A few studies in developing countries, such as Thailand and Indonesia (Dong et al, 2011), support the more extreme findings of Oczkowski et al (2020) of high DNRA and low-to-undetected levels of DNF, suggesting that low-latitude estuaries, like low-nutrient estuaries, likely respond differently to environmental controls than their temperate and even their subtropical counterparts.…”
Section: 1029/2020jg005766mentioning
confidence: 99%
“…Additionally, 83% were located in the Northern Hemisphere, Atlantic systems, and a massive 95% of the study sites were located in eutrophic or hypereutrophic systems (annual N load > 20 g N m −2 year −1 , Figure 1). By comparison, the data available from tropical and low‐nutrient or oligotrophic estuaries (annual N load < 20 g N m −2 year −1 ) are incredibly limited (Cook et al, 2004; Eyre et al, 2011; O'Meara et al, 2017; Oczkowski et al, 2020; Thomson et al, 2012). Additionally, a large proportion of studies in low‐nutrient systems are now nearly 30 to 40 years old and employed out‐of‐date methods such as the acetylene block technique (e.g., Kaspar, 1983; Kieskamp et al, 1991; Koch et al, 1992), making direct comparisons to modern studies difficult (Groffman et al, 2006).…”
Section: The Eutrophication Problemmentioning
confidence: 99%
See 3 more Smart Citations